A Historical Perspective from Folklorist Henry Glassie: Roots of Folk Songs in Music Education. Issue 1 (October 2022) - Cicco, M.M.Ed., Ian
The purpose of this study was to examine the sociocultural roots of folk songs from the perspective of renowned folklorist Henry Glassie. Dr. Henry Glassie holds the rank of Professor Emeritus at Indiana University, where he previously served on the faculty for the Department of Folklore and Ethnomusicology. Primary sources included Glassie's archived collection of folk song transcriptions, recordings, and field notes from the Appalachian region between 1961-1967, housed at the Archives of Traditional Music at Indiana University. A total of 1, 665 titles from elementary general music sources were cross-referenced with Glassie's collection, 26 of which appeared in the archived account. Two oral history interviews with Glassie revealed that folk songs that are commonly used in elementary general music classrooms have historical roots of which teachers may be unaware. The songs in this study raise ethical and moral questions regarding their use in the general music classroom and suggest that teachers carefully research folk songs and their related meanings.